Exploring Tutor’s Experience in Online Tutorial: Chances and Challenges - Ningrum, Siti Utami Dewi; Sekarwinahyu, Mestika; Wulandari, Nisa A’rafiyah Tri; Mukhtar, Mutia Kamalia (International Journal of Multidisciplinary Research of Higher Education, 2025)
Online tutorials are crucial for sustaining quality distance education in higher education. Evaluating tutor experiences is essential to determine the long-term viability of online learning in the future.   This research aims to evaluate the effectiveness of online tutorials from tutors' perspectives in the Universitas Terbuka General Courses Study Program in Basic Social and Cultural Science, Pancasila, and Civic Education courses. This study employs an explanatory sequential mixed-method approach to investigate the effectiveness of an online tutorial system. In the first phase, a survey was conducted to assess six key aspects; i) content quality, ii) ease of access, iii) interaction and communication, iv) evaluation and assessment, v) platform support, and vi) institutional support. The survey involved 344 tutors selected using accidental sampling. The collected data were analyzed using descriptive statistics with IBM SPSS Statistics 27.0.1. In the second phase, a qualitative study was conducted to provide a deeper understanding of the survey results. Qualitative data were collected through document analysis of online tutorial reports and interviews with 30 tutors selected through purposive sampling. The qualitative data were analyzed using thematic analysis to identify key themes from the interviews.   The study results showed that some of the main barriers tutors face include network and online tutorial page constraints and variations in student understanding of the material being taught. In addition, tutors also identified the need for training and technical support improvements to optimize the use of e-learning platforms. These findings suggest the need for improvements in technological infrastructure, regular tutor training, and the development of more interactive, adaptive learning methods. These recommendations aim to enhance the effectiveness of online tutorials and contribute to a more efficient distance-learning process at Universitas Terbuka.